ROAD TRAFFIC ACCIDENT ANALYSIS O THE JAKARTA-CIKAMPEK TOLL ROAD - Siboro (NIM 26990015), Halley
ABSTRACT: Highway Toll Roads are relatively new in Indonesia. Their high standard of design is believed to differentiate their accident characteristic from common road. This thesis aimed to identify accident and safety problem on The Jakarta-Cikampek Toll Road. The study was concerned with the classification and analysis of road traffic accidents data on Jakarta-Cikampek Toll Road. They consisted of data from October 1988 up to September 1989 when the section between Cibitung and Cikampek was single-carriageway, and from April 1991 up to March 1992 when the whole length of toll road was completely dual-carriageway. The former is defined as Period I and the latter is Period II. Compilation using several methods were carried out to obtain the appropriate data that could describe accident and safety problem on this toll road. The Definition for Coding Accidents (DCA) was used to identify the type of accident based on their movement. From data analysis, it is found that in Period I, the accident rate in general were higher in the single-carriageway section than in dual-carriageway operation. Comparison of accident rate between Period I and Period II shows higher accident rate for Period I for total, fatal and serious accidents, especially in single-carriageway section. The most significant factor causing accident on this road in both periods of study were human error i.e. drowse and careless drivers. These were strengthen by other factors i.e. driving at night, straight geometric condition, variation of vehicle speed, high traffic volume; and vehicular factor i.e. tire burst. Single vehicle accidents were the most frequent type of accident. The study gives recommendations to give remedies for the obtained conclusion and for improvement of future accident study and recording.